The recognition of the human right to a clean, healthy and sustainable environment at the international level. The road to resolution A/HRC/RES/48/13 of the Human Rights Council of October 2021. - Duncan Villalobos, Shara (2022)
On October 8, 2021, the United Nations Human Rights Council passed a resolution recognizing, for the first time at the international level, the human right to a clean, healthy and sustainable environment. The resolution, led by Costa Rica on behalf of a group of proponent countries, constitutes a historic milestone that will strengthen the inescapable link between human rights and the environment, in addition to supporting the creation of minimum standards of protection for all people in all regions of the world. The right to a clean, healthy and sustainable environment is the continuation of a process that began with the adoption of the Stockholm Declaration of 1972 and continued with the approval of the Rio Declaration of 1992. Despite being recognized in 155 legal different legal systems, this right has had to be studied linked to others rights such as life or health, and not as a right on its own, due to the lack of consideration at the international level. It is possible that in the coming months we will witness recognition in other forums, due to the context of environmental and biodiversity crisis in which we live, and the current concern about the effects of climate change on life on the planet, as well as on the full enjoyment of human rights. This article aims to share with readers the general context and some details of the negotiations in Geneva.